Gambaran Obat Tradisional yang Digunakan Penderita Malaria di Wilayah Puskesmas Simpang IV Sipin Kota Jambi 2014 - Darmawan, Armaidi; ., Lipinwati (JAMBI MEDICAL JOURNAL "Jurnal Kedokteran dan Kesehatan", 2014)
ABSTRACT Background: Traditional medicine is the ingredients derived from plants, animals, minerals or mixtures of these materials. Malaria is an infectious disease caused by Plasmodium parasites that invade erythrocytes and characterized by the discovery of asexual blood forms. At Jambi province, the morbidity due to malaria is still quite high. There are nine districts and two municipalities which is a malaria endemic area. The proportion use of traditional medicine for malaria is still unknown include Jambi province. The number of people and the efficacy of using a traditional medicine remains unknown. This research designed in order to describe the use of traditional medicine in patients with malaria. Methods: The type of this research is descriptive quantitative research. The study was conducted at the Puskesmas Simpang IV Sipin Jambi. The entire study of population malaria patients that visiting Puskesmas Simpang IV Sipin and home visit patients who had suffered from malaria in the month of November 2013-February 2014. The number of samples in this study is 70 respondents. Data were analyzed by univariate analysis. Result: From the results, users of traditional medicine as much as 34.5%, traditional types of drugs most widely used is the use of sambiloto (27.1%), the most reason way the patients take traditional medicine because the side effects are relatively small (35.7%), the most way to mix the ingredients is by blend the ingredients together boiled it whit water, after that patients drunk the potions (80%), the most way to find the ingredients is looking around the house (80%), the most duration of using traditional medicine expressed by respondents is for 3 days (41.4%), and 95.7% expressed the feeling that the traditional treatment is efficacious. Conclusion: The results stated that the description of the use of traditional medicine in Puskesmas Simpang IV Sipin is 34.5%.   Keywords: Traditional medicine, malaria